Faktor-Faktor Kepatuhan Pajak Terhadap Insentif Pajak Sebagai Moderasi Dengan Pelaku UMKM Di Wilayah Kabupaten Brebes - Widha Fitria; Achmad Badjuri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
One of the regions in Indonesia with a fairly high growth of MSMEs is Brebes, Central Java. UMKMs in Brebes district continue to increase from 2016 to 2021. This research was conducted to determine the effect of tax understanding, income turnover and digitization of tax services using tax incentives as moderation. This study used a quantitative method with the sampling technique used was purposive sampling and obtained a number of 100 samples of UMKM’s in the Brebes area. As for the analytical method used in this study is descriptive statistical analysis and moderated regression analysis.. The result of this study is that tax understanding has a significant positive effect on taxpayer compliance. Then income turnover has a significant positive effect on taxpayer compliance. Furthermore, digitalization of tax services has no significant positive effect on taxpayer compliance. Meanwhile, tax incentives have a significant positive effect on tax understanding of taxpayer compliance. However, tax incentives do not have a significant positive effect on income turnover on taxpayer compliance. While tax incentives do not have a significant positive effect on digitalization of services on taxpayer compliance. Keyword : Tax understanding, income turnover, digitalization of services, tax incentives, taxpayer compliance.